2023
DOI: 10.1002/ijgo.14991
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal health among pregnant patients in the context of a migratory crisis

Abstract: ObjectiveTo compare maternal and perinatal outcomes of migrant Venezuelan women with local pregnant patients in a Colombian institution in the context of a migratory crisis.Study DesignThis cross‐sectional study included 11 304 deliveries from the Clínica de Maternidad Rafael Calvo in Cartagena de Indias, Colombia, a tertiary referral center on the north coast of Colombia. Data on maternal demographics and perinatal outcomes were obtained by chart review.ResultsIn total, 595 patients were identified as Venezue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Migrant pregnant women are considered highly vulnerable and to have greater healthcare needs in terms of monitoring pregnancy. Studies have shown that migration during pregnancy may result in more adverse maternal and perinatal outcomes [ 5 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migrant pregnant women are considered highly vulnerable and to have greater healthcare needs in terms of monitoring pregnancy. Studies have shown that migration during pregnancy may result in more adverse maternal and perinatal outcomes [ 5 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with Venezuelan migrants in South American countries have shown that access to healthcare services is more complicated among migrant populations. Social integration, language barriers and discrimination are factors associated with inequality in healthcare delivery [ 9 ], and these factors are also associated with worse health outcomes [ 10 ]. Furthermore, illegal migrants face even more difficulties in accessing medical care due to their immigration status and lack of documentation in the host country [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reflecting the global scope of the problem, this issue contains, among others, reports from South Korea, Pakistan, India, Afghanistan, Mexico, Colombia, Palestine, and Turkey on SRHR outcomes, mitigation and response strategies to crisis 2–11 . Included articles highlight the vulnerability of refugees 12 and the disastrous impact regime change can have on access to services and maternal outcomes 5 .…”
mentioning
confidence: 99%